A perfectly matched layer technique for lattice Boltzmann method - Najafi-Yazdi, Alireza; Mongeau, Luc (Canadian Acoustics, 2008)
A boundary condition was developed based on the perfectly matched layer (PML) concept introduced by Berenger, for numerical simulations of electro-magnetic fields. The PML was developed with the help of the Lattice Boltzmann Method (LBM), which is a computational technique in fluid dynamics. The PML can creates absorbing layers for the theoretically non-reflective for any angle and frequency of incident wave. The LBM has proved some advantages over conventional Navier-Stokes schemes such as ease of parallel implementation, where the hydrodynamics properties as density, momentum, kinetic energy, and others can be obtained by different moments of the equilibrium distribution function in the phase space. The study showed excellent results in all cases, including the propagation of a Gaussian pulse.